Credit constraints and smallholder maize production in Ghana. (1st January 2014) - Awunyo-Vitor, Dadson; Al-Hassan, Ramatu M.
The study examined constraints influencing farmers' access to credit and the effect that credit has on maize productivity, using the endogenous switching regression approach with survey data collected from 595 maize farmers in the Ashanti and BrongAhafo Regions of Ghana. The study revealed that credit constraint has a dampening effect on input use and farm productivity. The results showed that engagement in off-farm income generating activities, farm size and farmers' perception on operational modalities are factors that influence credit constraint conditions for farmers. In addition, the marginal productivity of credit differs between credit-constrained and credit-unconstrained farmers: thus, access to credit would enable credit constrained farmers to take advantage of the available productive opportunities and increase maize productivity. Therefore, farmers in need of additional credit should be served to increase farm productivity.